2019
DOI: 10.1186/s12944-019-1150-0
|View full text |Cite|
|
Sign up to set email alerts
|

Bee pollen and propolis improve neuroinflammation and dysbiosis induced by propionic acid, a short chain fatty acid in a rodent model of autism

Abstract: BackgroundNeuroinflammation plays a major role in the pathogenesis of autism because the cytokine levels are typically disturbed in the brain in autistic patients. Prebiotics-rich diet maintains the healthy gut microbiota and hence can regulate the neuroinflammation indirectly. The study aimed to investigate the role of bee pollen and propolis in ameliorating neuroinflammation, including cytokine levels, in an animal model of autism.MethodsHamsters were classified as four groups: Group I, control; Group II, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…This shows the amelioration effect of the bee pollen and probiotics mixture against PPA‐induced neuroinflammation. This is in good agreement with (Aabed, Bhat, Al‐Dbass, et al., 2019 ; Aabed, Bhat, Moubayed, et al., 2019 ) which bee pollen showed a decrease in IL‐6 levels compared with PPA‐treated hamsters, as well as (Hegazi et al., 2015 ) whom reported the active substances of bee pollen which can act upon immunity responses. In probiotic case, Lactobacillus plantarum was able to reduce IL‐6 levels caused by ethanol‐induced neuroinflammation (Shukla et al., 2020 ), also Magistrelli et al.…”
Section: Discussionsupporting
confidence: 89%
“…This shows the amelioration effect of the bee pollen and probiotics mixture against PPA‐induced neuroinflammation. This is in good agreement with (Aabed, Bhat, Al‐Dbass, et al., 2019 ; Aabed, Bhat, Moubayed, et al., 2019 ) which bee pollen showed a decrease in IL‐6 levels compared with PPA‐treated hamsters, as well as (Hegazi et al., 2015 ) whom reported the active substances of bee pollen which can act upon immunity responses. In probiotic case, Lactobacillus plantarum was able to reduce IL‐6 levels caused by ethanol‐induced neuroinflammation (Shukla et al., 2020 ), also Magistrelli et al.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of the current study is of great support to our previous work in which vitamin D, CoQ10, vitamin B12, carnitine, and bioflavonoids (as major components of bee pollen) demonstrate significant potency in ameliorating PPA-induced persistent autistic features in the rodent model [77][78][79][80][81][82][83][84].…”
Section: Discussionsupporting
confidence: 88%
“…While the results of this study showed that BP in BP100/200+DOX groups caused a systemic increase in cytokines (GM‐CSF, G‐CSF, and IL‐10) that stimulate hematopoietic progenitor (HP) cells It also reduced the level of ROS‐mediated pro‐inflammatory cytokines (IL‐6 and IL‐1β) in the BM. Aabed et al., (2019) in a study on the protective effects of BP on propionic acid (PPA)‐induced neuro‐inflammation in a rodent model of autism showed that BP can decrease systemic IL‐6, IFN‐γ and IL‐1α alongside increase IL‐10 and TNF‐α levels thereby suppressing the inflammatory pathways mediated by cytokines leading to proliferation and activation of immune cells from BM haematopoietic progenitor (HP) cells which ameliorating the neurotoxic effects of PPA. In an in vitro study of LPS‐Induced RAW 264.7 cells, Lee et al., (2020) showed that BP, in addition to its high antioxidant properties and reduced NO content, iNOS and cyclooxygenase‐2 (COX‐2), reduced IL‐1b, IL‐6 and TNF‐α levels as inflammatory mediators in macrophages.…”
Section: Discussionmentioning
confidence: 99%